Dynamic factors in economic growth - Lewis, W. Arthur (Bombay : Orient Longman, 1974)
This volume comprise of three lectures (implementing a development plan, growth and income distribution, and exports and growth) delivered by Sir W Authur Lewis at the Dorab Tat Memorial Lectures in Delhi, India on 29th, 31st October and 7th November 1973.
ne 30/04/2019
Loans
Keywords: Income; Income distribution; Economic growth; Exports; Developing countries; India